Ensinando habilidades de prevenção a sequestro para adolescentes neuro divergentes a partir do Behavioral Skills Training (BST) - Coelho, Caroline Luiza (2025)
The onset of adolescence is a period in life where humans, whether neurodivergent or neurotypical, undergo various challenging changes in intrapersonal and interpersonal relationships. Some difficulties that neurodivergent individuals may face are related to the social skills necessary for maintaining their own safety in potentially dangerous situations, such as fires, harassment and even kidnappings (Mechling, 2008; Gimenes Júnior, 2016). An alarming statistic is that 424,066 adolescents are kidnapped annually since 2019 (Kutlu and Kurt, 2021), and due to this, the neurodivergent population could benefit from learning antikidnapping safety strategies. The objective of this study was to evaluate the effectiveness of teaching three kidnap-safety behaviors through Behavioral Skills Training (BST) for neurodivergent adolescents, through a systematic replication of Gunby et al. (2010) experiment, and to verify whether the generalization of such behaviors occurs and their maintenance over time, also assessing social validity among adolescents, caregivers, and the implementers of the procedure. The participants were two neurodivergent adolescents, and data collection was conducted through kidnapping tests during baseline phases and after teaching (that occurred through instruction, video modeling, behavioral rehearsal, and feedback). During the kidnapping tests and teaching via BST, safety behaviors were scored from 0 to 4, with “0” representing being kidnapped and “4” representing the emission of all safety behaviors: refusing, moving away from the kidnapper and reporting the situation to a trusting adult. The results indicated that the BST sessions taught safety behaviors to the adolescents, who previously scored from 0 to 2 (were kidnapped or at most refused the call), and after training, scored 4 (emitting all taught safe behavior topographies) also in different environments from the initially trained and over time, up to one-month post-learning. The variables that were relevant for the change of behaviors among participants beyond the teaching process were the participant´s discriminative repertoires of known and unknown faces, the recurrence of kidnapping tests that increasingly familiarized adolescents with dangerous situations, the use of reinforcing and corrective consequences for correct and incomplete performances, the use of different types of lures for kidnapping, the reinforcement history of rule-following, and the location of each kidnapping test. Moreover, despite the differences in results, both participants learned the anti-kidnapping responses and reported at the end of the study that they found it important for dangerous situations to be reported to known adults. Their family members and the adult confederates of the research found the procedure positively curious, because the teaching format used went beyond "mere instruction" of what should or shouldn’t be done, moving towards behavioral rehearsals and teaching using videos, visual resources, and feedback. Additionally, they describe that similar procedures can also be useful for teaching adolescents how to behave in other dangerous situations, such as those experienced online. Thus, this study aims to advance in the research area of anti-kidnapping safety skills taught to adolescents by the BST procedure through implementing methodological changes cited in previous studies and applying teaching to the Brazilian population